(untitled) (KYAMC Journal, 2017)
Objective: To demonstrate complications and difficulties that had been encountered during major gynaecological surgery. Materials & Methods: This retrospective hospital based study was carried out in the department of Obstetrics & Gynecology of Rajshahi Medical College & Hospital, Rajshahi, between 1st January 2002 to 30th june 2002. Result: Among 266 operated patients during the above mentioned 6 months period 100 samples were taken randomly. Regarding age distribution of the operated patients, 38% were in the age group of 31 to 40 years, more than ¼ th (33%) were in the age group of 41 to 50 years. Out of 100 patients about half (54%) of them were in the parous group of 1 - 5 children, next to this 28% had more than 5 and above babies. After sugery, 70 patients had no postoperative complications; only in 30 patients minor complications were noted. Among these, pyrexia above 100.0F was noted in 15 patients, lower abdominal pain in 8 patients and urinary tract infection in 5 patients. Conclusion: This study revealed a low rate of complications and difficulties encountered during major gynaecological surgery. In most cases due to highly skilled personnel, improvement of surgical technique, safe anaesthesia and appropriate use of antibiotics with blood transfusion, the mortality rate has remarkably decreased to nil. KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 444-448